Physical link between effective viscosity and electrical resistivity for dislocation creep in upper mantle and its application in Northwest Xinjiang, China - Li, Man; Xu, Yixian; Liu, Lian; Yang, Bo; Zhang, Yi; Zhu, Yixin; Liu, Shuyu (Geophysical journal international, 2025)
Effective viscosity of the upper mantle is a critical parameter for comprehending the dynamics of the lithosphere and plate tectonics. In recent years, magnetotelluric (MT) surveys have gained attention as a potential tool for determining viscosity. However, a direct physical basis for the relationship between effective viscosity and electrical resistivity still needs to be improved. To address this issue, we have established the basis that connects electrical resistivity and effective viscosity under different thermochemical conditions and the principle of electrical neutrality. The creep and electrical conductions of rocks in the lithospheric mantle are all the thermally activated atomic-scale random motion of particles in solids or melts, controlled by the slowest and fastest particles, respectively. Due to the sizeable electrostatic interaction energy, the concentrations of the two particles must always satisfy the charge-neutral condition. Hence, we derived two ideal models for anhydrous and hydrous olivine. Then, to demonstrate their applicability, we converted the resistivity cross-section constructed from long-period MT data to the effective viscosity distribution in the Tarim–Tianshan–Junggar area. We found that the results matched those obtained by the previous method well. Overall, this study provides valuable insights into the potential of MT surveys for determining the effective viscosity of the upper mantle.